2018
DOI: 10.1016/j.exer.2018.06.001
|View full text |Cite
|
Sign up to set email alerts
|

High fat diet induces pre-type 2 diabetes with regional changes in corneal sensory nerves and altered P2X7 expression and localization

Abstract: Type 2 diabetes is one of the leading pathologies that increases the risk of improper wound healing. Obesity has become a major risk factor for this disease that is now considered to be the 4th highest cause of preventable blindness according to the World Health Organization. The cornea is the most densely innervated structure in the human body and senses even the slightest injury. In diabetes, decreased corneal sensitivity secondary to diabetic peripheral neuropathy can lead to increased corneal abrasion, ulc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 42 publications
(76 reference statements)
5
24
0
Order By: Relevance
“…It serves as a pain receptor. Kneer et al 2 previously reported that P2×7 mRNA was significantly overexpressed in diabetic human corneas compared with controls. Therefore, the authors hypothesized that the P2×7 receptor acts to sense changes at the leading edge following an epithelial abrasion, with this form of regulation lost in diabetic eyes.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…It serves as a pain receptor. Kneer et al 2 previously reported that P2×7 mRNA was significantly overexpressed in diabetic human corneas compared with controls. Therefore, the authors hypothesized that the P2×7 receptor acts to sense changes at the leading edge following an epithelial abrasion, with this form of regulation lost in diabetic eyes.…”
Section: Resultsmentioning
confidence: 95%
“…Diabetes alters corneal nerve structure44 and downregulate the release of neuropeptides, neurotrophins and growth factors 45. Kneer et al 2 reported a significant decrease in cornea sub-basal nerve density in DIO mice compared with controls, demonstrating similar established phenotypes to that of human diabetics. In this study, a DIO mouse model of type 2 diabetes was used to characterize changes in sensory nerves and P2X purinoceptor 7 (P2×7).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…An alteration in purinergic receptor subtype expression patterns has been observed in diabetes in the retina and other tissues (Ho et al, ; Kneer, Green, Meyer, Rich, & Minns, ; Mankus, Rich, Minns, & Trinkaus‐randall, ; Seref‐ferlengez, Maung, Schaffler, & Spray, ; Vindeirinho, Santiago, Cavadas, Ambrósio, & Santos, ). For example, in diabetic animals, an increase in levels of P2X 7 R has been reported in corneal epithelium (Kneer et al, ; Mankus et al, ), although a decrease in the expression of these receptors also was shown in osteocytes under HG conditions (Seref‐ferlengez et al, ). Likewise, the metabotropic receptors P2Y 2 R and P2Y 4 R suffer an overexpression in osteoblasts under diabetic conditions (Seref‐ferlengez et al, ), as do some adenosine receptors in the retina (Vindeirinho, Costa, Correia, & Santos, ).…”
Section: Discussionmentioning
confidence: 99%